Customer intention berkunjung ke Cafe & Resto: peran social media marketing - Iva Nurdiana Nurfarida; Endi Sarwoko (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2022)
The research aims to investigate the effect of social media marketing on the intention to visit Cafe & Resto, and to analyze the role of brand awareness as mediation. The research was conducted at random Cafe & Resto in Malang City, data was collected using a questionnaire by utilizing social media. Hypothesis testing using Path Analysis. The results of the study show that the use of social media marketing is able to encourage customer intention to visit Cafe & Resto, besides that social media marketing also increases customer/consumer brand awareness of Cafe & Resto, and increased brand awareness provides benefits to increased customer intention. Brand awareness acts as a mediator for the influence of social media marketing on customer intention. The research has theoretical and practical implications and is discussed further in this article.